Single dose oral toxicity study of ethanolic extract from inflorescence of Casuarina equisetifolia in Wistar rats - Umamaheswar Rao, O.; Chinna Eswaraiah, M. (Journal of Drug Delivery and Therapeutics, 2018)
The purpose of the study was to evaluate the single dose oral toxicity of the ethanolic extract from inflorescence of Casuarina equisetifolia, Family: Casuarinaceae in female Wistar Rats. The acute toxicity study was carried out based on Organization for Economic Co-operation and Development (OECD) Test Guideline 423. However, this plant safety evaluation data was not available so, selected the starting dose from 300 mg/kg body weight. The animals were orally administered a single dose of 300 mg/kg body weight and followed by 2000 mg/kg body weight in next step. Signs of toxicity and mortality were observed after 30 min, 1, 2, 4 and 24h of administration of the extract and once daily for 14 days. There was no mortality in the tested animals and no abnormal clinical signs were observed related to test item. No abnormalities were detected in gross pathology observations in all the rats at both the dose levels. Based on observations of the present study, it can be concluded that the LD50 of ethanolic extract from inflorescence of Casuarina equisetifolia is greater than 2000mg/kg body weight and can be classified as Category 5; however, further studies are needed to confirm long term toxicities.Keywords: Acute oral toxicity, ethanolic extract from inflorescence of Casuarina equisetifolia, LD50, OECD Test Guideline, Wistar Rat.